COMPARATIVE STUDY OF THE RELATIVE CONDITION FACTOR IN TWO AIR BREATHING FISHES FROM SORAON LAKE : A CASE STUDY - PANDEY, A. C.; SHARMA, M. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
An analysis of the relative condition factor (Kn) values showed that Anabastestidineus performed better (54% population having Knvalues more than 1 and 46% less than 1. Kn range 0.8976-11039 with mean value of 1.0017) than Saccobranchus fossilis (46%population having Knvalues above 1 and 54% belowl, Knrange 0.8172-10878 with an average of 0.9850)under the natural conditions of Soraon lake (Faizabad).